The impact of water scarcity on support for hydraulic fracturing regulation: A water-energy nexus study. (November 2020) - Hannibal, Bryce; Portney, Kent
Abstract: The rise of unconventional oil and gas development in the form of hydraulic fracturing, or fracking, has drawn much attention from media, scholars, and policy makers, and Texas has frequently been the epicenter of this attention. This paper looks at fracking through a particular lens, that of an extraction process that relies heavily on water. This "water-energy nexus" has been studied in terms of the physical connections, but little research exists on how ordinary people might understand that nexus. This paper examines the effect of people's awareness of the water-energy nexus and county-level drought characteristics on their support for increased regulation of water issues associated with hydraulic fracturing. The analysis uses data from a Texas-based public opinion survey, and county-level data from the U.S. Drought Monitor and the Texas Railroad Commission. Multi-level modeling techniques are used to examine the impact of proximity, local water scarcity, and individual awareness of the water-energy nexus on people's willingness to support regulating aspects of water in hydraulic fracturing practices. The paper supports the hypothesis that individual awareness of the energy-water nexus and local water scarcity affects willingness to support greater regulation and concludes with some policy recommendations to improve policy transparency surrounding hydraulic fracturing. Highlights: Texas Residents support increased regulation on hydraulic fracturing. Water-energy nexus awareness results in more support for regulating fracking. Counties experiencing drought support regulation for fracking's impact on water.